Memory: A Universal Concept but Limitedly Known. - Faghankhani, Masoomeh (Journal of Memory, 2018)
A broad essay surveys the concept of memory across disciplines. It distinguishes short‑ and long‑term processes and reflects on measurement limits and open questions.
Keywords: Memory; Short-Term; Long-Term; Measurement Limits